Endovascular treatment of intracranial vascular malformations in children. (12th June 2020) - Lubicz, Boris; Christiaens, Florence
Abstract : Paediatric intracranial vascular malformations are rare and different from adult ones in vascular anatomy, pathophysiology, and symptoms. Their impact on the brain and their symptoms will differ in the antenatal period, in neonates, infants, and children. Clinical presentation includes seizures, focal neurological deficit, haemorrhage, congestive heart failure, hydrovenous disorder, and developmental delays. These malformations are thus associated with a poor prognosis if left untreated. Therefore, aggressive management is generally recommended and must be performed by a multidisciplinary team with extensive experience. Endovascular treatment is the first‐choice treatment for most paediatric intracranial vascular malformations. Indication and timing for treatment should be decided on the basis of a careful assessment of neurological symptoms, growth and development, cardiac and other systemic manifestations, and imaging of the malformation and the brain tissue. What this paper adds: Paediatric intracranial vascular malformations are rare, but their prognosis is poor if left untreated. Improved clinical, anatomical, and pathophysiological understanding of these complex lesions has improved prognosis. What this paper adds: Paediatric intracranial vascular malformations are rare, but their prognosis is poor if left untreated. Improved clinical, anatomical, and pathophysiological understanding of these complex lesions has improved prognosis.